1990
DOI: 10.1097/00001888-199001000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Winds of Change: Evaluating Innovative Medical Curricula

Abstract: The increased interest, in North America and around the world, in problem-based and community-oriented medical curricula has sparked interest in the evaluation of these innovative programs. In January 1989, the Josiah Macy Jr. Foundation sponsored a conference to consider designs for evaluation studies and the potential distinctive outcomes of the innovative curricula that might be foci of these studies. After defining an "innovative curriculum," the participants identified seven characteristics of "important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 0 publications
2
49
0
4
Order By: Relevance
“…Among these dilemmas, they found that educators and students were most concerned with the issues of depth versus breadth and factual knowledge versus higher-order thinking skills. These issues arose from PBL students' slightly less than desirable performances on content tests compared to traditional students (Albanese & Mitchell, 1993;Friedman et al, 1992;Levesque, 1999;Vernon & Blake, 1993), as well as teachers' (Angeli, 2002) and students' (Dods, 1997;Lieux, 2001;Schultz-Ross & Kline, 1999) concerns with respect to sufficient content coverage in a PBL curriculum. Although some studies indicated that sufficient breadth of content acquisition was not sacrificed for depth of content learning (Gallagher & Stepien, 1996), others suggested that more balance was necessary (Dods, 1997).…”
Section: Contentmentioning
confidence: 99%
“…Among these dilemmas, they found that educators and students were most concerned with the issues of depth versus breadth and factual knowledge versus higher-order thinking skills. These issues arose from PBL students' slightly less than desirable performances on content tests compared to traditional students (Albanese & Mitchell, 1993;Friedman et al, 1992;Levesque, 1999;Vernon & Blake, 1993), as well as teachers' (Angeli, 2002) and students' (Dods, 1997;Lieux, 2001;Schultz-Ross & Kline, 1999) concerns with respect to sufficient content coverage in a PBL curriculum. Although some studies indicated that sufficient breadth of content acquisition was not sacrificed for depth of content learning (Gallagher & Stepien, 1996), others suggested that more balance was necessary (Dods, 1997).…”
Section: Contentmentioning
confidence: 99%
“…Pengetahuan dan keterampilan akan berkembang seperti spiral. Kesulitan dalam ujian ilmu pengetahuan dasar (biomedik) dibandingkan kurikulum konvensional dapat diatasi sesuai dengan Mennin et al (1993) 20 yang menyatakan metode teacher-centred dan terstruktur dapat lebih baik dalam mengajarkan ilmu biomedik dasar. Sehingga pada masa adaptasi awal mungkin perkuliahan tetap diberikan dalam jam yang relatif lebih banyak.…”
Section: Hambatan Pblunclassified
“…Friedman et al [11] ont également montré que l'APP permet aux étudiants d'atteindre des habiletés interpersonnelles supérieures, une plus grande pratique de l'apprentissage continué et un plus haut niveau de satisfaction professionnelle. Plus récem-ment, Haak et al [12] ont montré que l'APP appliqué en biologie facilitait l'apprentissage et diminuait la disparité entre étudiants avec des connaissances initiales inégales.…”
Section: Problématiqueunclassified